Acquisition of antibodies that block Plasmodium falciparum adhesion to placental receptor chondroitin sulfate A with increasing gravidity in Malian women - Mahamar, Almahamoudou; Traore, Moussa; Swihart, Bruce; Attaher, Oumar; Diarra, Bacary Soumana; Santara, Gaoussou; Issiaka, Djibrilla; Barry, Amadou; Sidibé, Youssoufa; Dicko, Yahia T.; Keita, Sekouba; Ndiaye, Oulematou; et al. (Frontiers in Immunology, 2024)
In malaria-endemic areas, pregnant women are more susceptible to Plasmodium falciparum infection, especially primigravidae. During pregnancy, parasites sequester in the placenta and bind to the receptor chondroitin sulfate (CSA). This unique adhesion is mediated by the parasite protein VAR2CSA expressed on the surface of infected erythrocytes (IE). Placental malaria is associated with poor pregnancy outcomes including perinatal mortality, preterm delivery, small for gestational age (SGA) and low birthweight deliveries. Over successive pregnancies, women acquire functional antibodies that inhibit IE adhesion to CSA. Here, we examine the development of anti-adhesion activity and the breadth of anti-adhesion activity as a function of number of previous pregnancies, using samples collected from pregnant women living in an area with high seasonal malaria transmission. Women reached plateau levels of anti-adhesion activity and breadth of anti-adhesion activity after 5 pregnancies. We related the level of anti-adhesion activity and reactivity with surface IE to SGA 19/232 pregnancies resulted in SGA, and report that an increase of 10% in median anti-adhesion activity reduced the odds of SGA by 13% and this relationship approached significance. Further, at an anti-adhesion activity level of 43.7%, an increase of 10% in the breadth of activity significantly reduced the odds of SGA by 21.5%. Antibodies that recognize IE surface increased over successive pregnancies, but were not associated with a reduction in SGA. These results can serve as a guideline for assessing vaccine candidates aiming to reduce poor pregnancy outcomes associated with placental malaria.